PENGEMBANGAN MEDIA POP UP BOOK DIGITAL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PADA MATERI BANGUN RUANG SISI DATAR SISWA SMP KELAS VIII - Rahmawati; Dwi Oktaviana; Rahman Haryadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning media are tools or materials used by teachers in the classroom to facilitate the delivery of material more effectively. In this study, the media developed was tailored to the school’s needs based on preliminary observations, specifically a digital Pop-Up Book learning media. This research aims to examine the validity, effectiveness, and practicality of the digital Pop-Up Book learning media on flat-sided solid geometry material to improve the mathematical communication skills of eighth-grade students at SMP Negeri 1 Sungai Kakap. The type of research used is Research and Development (R&D) with a modified 4D method reduced to 3D, consisting of the define, design, and develop stages. The data collection techniques employed include measurement techniques, indirect communication, and direct communication. The instruments used consist of validation sheets, questionnaires, and tests. Data were analyzed using validity, practicality, and effectiveness tests. The validity test results showed a percentage of 83.3% categorized as very valid, the practicality test yielded 92.02% categorized as very practical, and the effectiveness test reached 80% categorized as effective.